Growth, morphology, ammonium uptake and nutrient allocation of Myriophyllum brasiliense Cambess. under high NH4+ concentrations - Saunkaew P. (2014)
The effects of high NH4+ concentration on growth, morphology, NH4+ uptake and nutrient allocation of Myriophyllum brasiliense were investigated in hydroponic culture. The plants were grown under greenhouse conditions for 4 weeks using four levels of NH 4+ concentration: 1, 5, 10 and 15 mM. M. brasiliense grew well with a relative growth rate of c.0.03 day-1 at NH4+ concentration up to 5 mM. At the higher NH4+ concentrations the growth of the plants was stunted and the plants had short roots and few new buds, especially when grown in 15 mM NH4+ where the submerged leaves were lost and there were rotten roots and submerged stems. To avoid NH4+ toxicity, the plants may have a mechanism to prevent cytoplasmic NH4+ accumulation in plant cells. The net uptake of NH4+ significantly decreased and the total N significantly increased in the plants treated with 10 and 15 mM NH4+, respectively. The plant may employ NH4+ assimilation and extrusion as a mechanism to compensate for the high NH4+ concentrations. However, the plants may show nutrient deficiency symptoms, especially K deficiency symptoms, after they were exposed to NH4+ concentration higher than 10 mM. The present study provides a basic ecophysiology of M. brasiliense that it can grow in NH4+ enriched water up to concentrations as high as 5 mM. © 2011 Springer Science+Business Media, LLC.